The effects of prenatal stress on Alpha4 Beta2 and Alpha7 hippocampal nicotinic acetylcholine receptor levels in adult offspring. Issue 11 (17th September 2013) - Schulz, Kalynn M.; Andrud, Kristin M.; Burke, Maria B.; Pearson, Jennifer N.; Kreisler, Alison D.; Stevens, Karen E.; Leonard, Sherry; Adams, Catherine E.
ABSTRACT Prenatal stress in humans is associated with psychiatric problems in offspring such as anxiety, depression, and schizophrenia. These same illnesses are also associated with neuronal nicotinic acetylcholine receptor (nAChR) dysfunction. Despite the known associations between prenatal stress exposure and offspring mental illness, and between mental illness and nAChR dysfunction, it is not known whether prenatal stress exposure impacts neuronal nAChRs. Thus, we tested the hypothesis that maternal stress alters the development of hippocampal alpha4 beta2 (α4β2∗) and alpha7 (α7∗) nicotinic receptor levels in adult offspring. Female Sprague‐Dawley rats experienced unpredictable variable stressors two to three times daily during the last week of gestation. At weaning (21 days) the offspring of prenatally stressed (PS) and nonstressed (NS) dams were assigned to same‐sex PS or NS groups. In young adulthood (56 days), the brains of offspring were collected and adjacent sections processed for quantitative autoradiography using [125I]‐epibatidine (α4β2* nicotinic receptor‐selective) and [125I]‐α‐bungarotoxin (α‐BTX; α7* nicotinic receptor‐selective) ligands. We found that PS significantly increased hippocampal α4β2* nAChRs of males and females in all subfields analyzed. In contrast, only females showed a trend toward PS‐induced increases in α7* nAChRs in the dentate gyrus. Interestingly, NS females displayed a significant left‐biased lateralization of α7* nAChRs in the laconosum moleculare of area CA1, whereas PS females did not, suggesting that PS interfered with normal lateralization patterns of α7* nAChRs during development. Taken together, our results suggest that PS impacts the development of hippocampal nAChRs, which may be an important link between PS exposure and risk for neuropsychiatric illness. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 73:806–814, 2013